Use for the Benefit of All? The Double-Edged Implications of Commercial Activities under the Outer Space Treaty - Putra Hamonangan Ritonga; Davilla Prawidya Azaria (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2026)
The 1967 Outer Space Treaty was drafted in the Cold War era, when States were the primary actors in outer space activities. Consequently, Article I’s concept of “use” referred mainly to peaceful and scientific exploration by States. In the New Space Era, however, private actors such as SpaceX and Blue Origin have shifted space activities toward profit-driven commercialization. This development creates normative tension with the Treaty’s principle that outer space shall be used “for the benefit of all countries,” as commercial practices risk deepening inequality, enabling technological monopolies, and increasing environmental threats, particularly space debris. This research employs a normative juridical method through library-based analysis of international legal instruments, national regulations, and academic doctrines, complemented by comparison with other global commons regimes, notably the United Nations Convention on the Law of the Sea. The findings show that the current interpretation of “use” is inadequate for regulating multi-actor commercial activities. Therefore, an ius constituendum is required to redefine and limit “use” through fair benefit-sharing, proportional responsibility, and sustainable protection of the outer space environment, drawing inspiration from institutional models such as the International Seabed Authority.